The Psychological Mechanisms Underlying Solomon’s Paradox: Impact of Mood and Self-Transcendence - Xu, Wentao; Zhang, Kaili; Wang, Fengyan (Frontiers in Psychology, 2022)
Solomon’s paradox of wise reasoning, in which performance of wisdom differs when reasoning on an issue in one's own life vs. another’s life, has been supported by robust evidence. However, the underlying psychological mechanism remains unclear. This asymmetry of wise reasoning may be explained by the different mindsets of self-transcendence when people reason about various conflicts (personal vs. others’), and mood should play a fundamental role. To explore this issue, three hundred ninety-nine participants were recruited to test a hypothesized model. The results supported the effect of Solomon’s paradox—that is, participants endorsed wise-reasoning strategies more strongly when resolving others’ social conflicts than their own. Further mediation analysis showed that the sequential mediation model was supported. Solomon’s paradox can be explained by the difference in positive affect and self-transcendence when reasoning about the two conflicts. This study directly verifies the mediating role of self-transcendence in Solomon’s paradox. At the same time, reasoning about personal affairs reduces individuals’ self-transcendence mindset, and positive affect can explain the differences. These results are helpful for understanding and effectively avoiding Solomon’s wisdom dilemma.